(untitled) - Myers, David G (Québec, Canada, 1992)
This modular version of Myers's full-length text, Psychology, reflects the author's research-supported belief that many students learn better using a text comprised of brief modules, as opposed standard-length chapters. Psychology, Eighth Edition, in Modules breaks down the 18 chapters of Psychology into 58 short modules, retaining that acclaimed text's captivating writing, superior pedagogy, and wealth of references to recent cutting-edge research. The modular version has its own extensive media and supplements package, with content organized to match its table of contents.
Keywords: Social interaction,Social psychology